The associations of fatty acids related dietary patterns with overweight and obesity among Chinese children - Zhi Huang; Keyu Ma; Xiaochen Yin; Ziming Li; Ming Chen; Yujie Duan; Li Li; Yuming Hu (BMC, 2024)
Abstract Background Childhood overweight and obesity is becoming an emerging face of malnutrition. The aims of this study were to develop fatty acid (FAs) related dietary patterns and explored the associations of FAs related dietary patterns with overweight and obesity among Chinese children. Methods An observational study was conducted on 435 children aged 4 to 7 years old in South Central China. Erythrocyte FAs composition was analyzed by gas chromatography-mass spectrometry. Diet was collected by food frequency questionnaires and dietary patterns were evaluated by reduced rank regression. The logistic regression analysis was used to exploring the association of dietary patterns with overweight and obesity. Results The prevalence of overweight, obesity, and overweight or obesity were 6.52, 4.59, and 11.11% in Chinese children, respectively. Twenty five types of FAs were detected in erythrocyte of children and four FAs related dietary patterns were identified. The dietary pattern positively correlated with n-3 PUFAs, but negatively with SFAs,was characterized by high intake of fish, shrimp, crab and shellfish, leaf-off vegetable, nuts, and tubers, which have a significantly decreased overweight risk (OR = 0.580, 95%CI: 0.375 ∼ 0.895, P = 0.014).The pattern positively strong associated with n-6 PUFAs, but negatively strong with n-3 PUFAs, had high intake of snacks, leaf-off vegetable, fresh beans, and coarse cereals, which have a significantly decreased obesity risk (OR = 0.518, 95%CI: 0.325 ∼ 0.827, P = 0.006). Conclusion Four FAs related dietary patterns were identified. The dietary pattern with high intake of fish, shrimp, crab and shellfish decreased overweight risk by increasing n-3 PUFAs, and decreasing SFAs. The dietary pattern with high intake of plant food, decreased obesity risk by providing an balanced n-6/n-3 PUFAs ratio.